Determinants of bank profitability in a developing economy: empirical evidence from Bangladesh - Sufian, Fadzlan; Habibullah, Muzafar Shah (Vilnius Gediminas Technical University (VGTU) Press Technika, 2009)
This study seeks to examine the performance of 37 Bangladeshi commercial banks between 1997 and 2004. The empirical findings of this study suggest that bank specific characteristics, in particular loans intensity, credit risk, and cost have positive and significant impacts on bank performance, while non‐interest income exhibits negative relationship with bank profitability. During the period under study the results suggest that the impact of size is not uniform across the various measures employed. The empirical findings suggest that size has a negative impact on return on average equity (ROAE), while the opposite is true for return on average assets (ROAA) and net interest margins (NIM). As for the impact of macroeconomic indicators, we conclude that the variables have no significant impact on bank profitability, except for inflation which has a negative relationship with Bangladeshi banks profitability.